Farmers' indigenous knowledge, perception and management practices of American fall army worm (Spodoptera frugiperda J. E. Smith) in maize crop productions in West Hararghe Zone, Ethiopia. (2020) - Urge, Misrak; Negeri, Mulugeta; Selvaraj, Thangavel; Demissie, Girma
No abstract available